Land Evaluation of Legume Growing Soils in Anantapuramu District of Andhra Pradesh, India by Integrating Remote Sensing and Geographic Information System - G. Sashikala; M.V.S. Naidu; K.V. Ramana; K.V. Nagamadhuri; A. Pratap Kumar Reddy; P. Sudhakar (Journal of the Indian Society of Soil Science, 2023)
Legumes play a greater role in sustaining the economy of the rainfed farming as compared to many other cereal crops. A detailed soil survey was conducted in legume (like groundnut (Arachis hypogaea L.), pigeonpea (Cajanus cajan L.) and chickpea (Cicer arietinum L.)) growing soils of Anantapuramu district, Andhra Pradesh, India by integrating remote sensing and geographic information system (GIS) to know the soil constraints that hinder the yields and to suggest an action plan to improve yields. Land evaluation parameters viz., USDA land capability classification and FAO soil suitability classification (actual and potential) were evaluated in the study area. Thematic land capability and crop suitability maps were mapped using Arc GIS software. Fourteen soil series were identified and further subjected to land evaluation studies. Three land capability classes (III, IV and VI) were identified. Actual suitability of groundnut, pigeon pea and chickpea falls under marginally suitable (S3) and not suitable (N) classes. The main soil limitations that affect the yield of these crops are rooting depth, drainage, gravelliness, erosion, pH, organic carbon (OC) and alkalinity. As these limitations override other good qualities and bring them to lower classes. By correcting the limitations, these soils can be elevated to highly suitable (S1), moderately suitable (S2) and marginally suitable (S3). The site specific thematic maps helps in suggesting suitability of particular crop variety, quantum of seeds to be made available and reduce the distress caused by ill-advised choices.